Vacuolar fructose transporter SWEET17 is critical for root development and drought tolerance. Issue 4 (16th September 2021) - Valifard, Marzieh; Le Hir, Rozenn; Müller, Jonas; Scheuring, David; Neuhaus, Horst Ekkehard; Pommerrenig, Benjamin
Abstract: Root growth and architecture are markedly influenced by both developmental and environmental cues. Sugars integrate different stimuli and are essential building blocks and signaling molecules for modulating the root system. Members from the SUGAR WILL EVENTUALLY BE EXPORTED TRANSPORTER (SWEET) family facilitate the transport of different sugars over cellular membranes and steer both inter and intracellular distribution of sugars. SWEET17 represents a fructose-specific sugar porter localized to the vacuolar membrane, the tonoplast. Here, we analyzed how SWEET17-dependent fructose released from vacuoles affects root growth during drought stress in Arabidopsis ( Arabidopsis thaliana ). We found that the SWEET17 gene was predominantly expressed in the root vasculature and in meristematic cells of the root tip. SWEET17 expression appeared markedly induced during lateral root (LR) outgrowth and under drought. Moreover, fructose repressed primary root growth but induced density and length of first order LRs. Consistently, sweet17 knock-out mutants exhibited reduced LR growth and a diminished expression of LR-development-related transcription factors during drought stress, resulting in impaired drought tolerance of sweet17 mutants. We discuss how SWEET17 activity integrates drought-induced cellular responses into fructose signaling necessary for modulation of the root system and maximal drought tolerance. Abstract : A vacuolar fructose transporter must be functional for proper lateral root development and maximal drought tolerance in Arabidopsis.